Sublingual drug dispensing prosthesis - Dhanraj Ganapthy; Padma Ariga; Anand Selvaraj (Wolters Kluwer Medknow Publications, 2012)
Sublingual mode of drug administration is one of the fastest and predictable methods of drug delivery to the patient. Some patients, due to the pathological or psychological reasons, experience considerable difficulty in retaining the sub-lingual tablets. Therefore, often they either swallow or chew the sublingual tablets, thus reducing the efficacy of the medicines. Sublingual drug dispensing prosthesis is a special type of appliance that helps such patients to house the sublingual tablets in special slots in an intra-oral appliance, and thus enhances proposed drug delivery and improves the patient's health.